The human Ha-ras oncogene induces genomic instability in murine fibroblasts within one cell cycle. - Denko, N C (1994)
Many human tumors contain an activating mutation in one of the ras protooncogenes. Additionally, these tumor cells are often heteroploid and characterized by chromosome breaks and rearrangements that are consequences of the genomic instability that is thought to contribute to tumor progression. The concurrence of ras mutations and genomic instability in tumors prompted us to ask whether selective induction of an activated Ha-ras gene could render a genome unstable. The NIH 3T3 cells used in this study contained mutant p53 genes and carried a selectively inducible activated (EJ) Ha-ras transgene under the control of bacterial lactose regulatory elements. When stably transfected cells were induced to express activated Ha-ras by isopropyl beta-D-thiogalactoside administration, there was a marked increase in the number of gross chromosomal aberrations including acentric fragments, multicentric chromosomes, and double minutes, which occurred within the time frame of a single cell cycle from the time of induction. To confirm that these aberrations occurred within the first cell cycle after mutant Ha-ras induction, the cells were arrested in G1 phase by serum depletion and, subsequently, released by administration of isopropyl beta-D-thiogalactoside or serum. The mitoses from cells released with isopropyl beta-D-thiogalactoside contained a 3-fold elevation in the fraction of chromosomes containing aberrations compared to mitoses from parallel cell cultures that were released with serum. Thus, the induction of activated Ha-ras gene expression in these cells results in genomic instability that can be detected as aberrant chromosomes at the next mitosis.